Isolation and Molecular Characterization of Two Arabinosyltransferases in Response to Abiotic Stresses in Sijichun Tea Plants (Camellia sinensis L.) - Liao, Tzu-Chiao; Chen, Chung-Tse; Wang, Mao-Chang; Ou, Shang-Ling; Tzen, Jason T. C.; Yang, Chin-Ying (Agronomy (Basel), 2023)
The modification of secondary metabolites is crucial to the function of metabolites in tea (Camellia sinensis L.). The arabinan deficient (ARAD) encodes an arabinosyltransferase and is involved in the arabinan biosynthesis pathway. Two full-length sequences of CsARADs were cloned and obtained from tea plants through the rapid amplification of cDNA ends and named CsARAD1 and CsARAD2. CsARAD1 and CsARAD2 are predicted to be 2 membrane proteins containing N-glycosylation, phosphorylation, and N-myristoylation sites and are 2 homologs of the glycosyltransferases (GT) 47 family, according to various bioinformatic analyses. CsARADs showed higher transcription levels in nonlignified tissues (e.g., buds and young leaves) than in old leaves and stems. CsARADs also exhibited the highest expression level in autumn, indicating that CsARAD regulation is affected by environmental factors. The transcript levels of CsARADs were changed after various abiotic stress treatments, and CsARAD1 and CsARAD2 displayed different regulation patterns in temperature stress, saline, and drought-like conditions. CsARAD1 and CsARAD2 were both significantly downregulated after tea seedlings were treated with an ethylene precursor and abscisic acid. In addition, CsARAD2 was downregulated after being treated with methyl jasmonate and gibberellin. Collectively, our findings on the function of arabinosyltransferase serve as a basis for further research and breeding applications.